The impact of repeated mismatches in kidney transplantations performed after nonrenal solid organ transplantation. Issue 1 (6th October 2017) - Côté, J. M.; Zhang, X.; Dahhou, M.; Sapir‐Pichhadze, R.; Foster, B.; Cardinal, H.
Abstract : The aim of this study was to determine whether kidney transplantations performed after previous nonrenal solid organ transplants are associated with worse graft survival when there are repeated HLA mismatches (RMM) with the previous donor(s). We performed a retrospective cohort study using data from the Scientific Registry of Transplant Recipients. Our cohort comprised 6624 kidney transplantations performed between January 1, 1990 and January 1, 2015. All patients had previously received 1 or more nonrenal solid organ transplants. RMM were observed in 35.3% of kidney transplantations and 3012 grafts were lost over a median follow‐up of 5.4 years. In multivariate Cox regression analyses, we found no association between overall graft survival and either RMM in class 1 (hazard ratio [HR]: 0.97, 95% confidence interval [CI] 0.89‐1.07) or class 2 (HR: 0.95, 95% CI 0.85‐1.06). Results were similar for the associations between RMM, death‐censored graft survival, and patient survival. Our results suggest that the presence of RMM with previous donor(s) does not have an important impact on allograft survival in kidney transplant recipients who have previously received a nonrenal solid organ transplant. Abstract : This retrospective cohort study shows that in patients who receive a kidney transplantation after a nonrenal solid organ transplantation, repeated HLA mismatches do not have an important impact on graft survival.